A Practical Method for Joint Inventory Replenishment under Supplier Constraints - Winter, T.S.; van Vuuren, J.H. (South African Journal of Industrial Engineering, 2025)
Retail distributors routinely encounter a variety of supplier constraints, including those related to the size and timing of inventory replenishment orders, such as minimum order quantities and minimum reorder intervals. In addition, constraints on the transportation of replenishment stock, such as minimum order values and container filling requirements, necessitate the joint replenishment of commodities in the case of multi-commodity inventories. These supplier constraints typically lead to larger order quantities and excess inventory, giving rise to the need for a joint replenishment model that is capable of mitigating the impact of increased inventory levels. In this paper, we propose a novel simulation-optimisation modelling approach in support of the complicated joint replenishment decisions faced by inventory managers in the presence of the aforementioned constraints. The modelling approach is capable of consolidating multi-product inventory replenishment orders, guided by minimum reorder intervals and minimum order quantities, subject to container filling and/or minimum order value constraints. It aims to optimise safety stock levels heuristically with a view to reducing the increased inventory costs associated with the particular supplier constraints imposed. We show in a real-world case study that the modelling approach is capable of leading to substantial cost savings during joint inventory replenishment decisions.